Using profanity and negative sentiments: An analysis of ultimate fighting championship fighters’ trash talk on fans’ social media engagement and viewership habits - Tereso, D.; Moro, S.; Ramos, P.; Calapez, T.; Costa, J. M.; Ratts, T. (International Journal of Sport Communication, 2022)
The rise in popularity of combat sports has afforded fighters an enhanced celebrity status, especially across online platforms that provide fans the opportunity to engage with and discuss their favorite athletes. Given this growth, fighters’ behaviors, both inside and outside of the arena, can have a strong influence on fans’ consumption and social media activity. To evaluate this relationship, this study investigated the effect of combat sports fighters’ trash talking on subsequent fans’ behaviors by collecting and analyzing 516 fighter responses during prefight press conferences and 32,360 fan tweets on Twitter during Ultimate Fighting Championship events. Results demonstrated that fights featuring polarizing and popular athletes generated the highest pay-per-view numbers, and higher levels of profanity speech during trash talking were associated with higher engagement in pay-per-view consumption and Twitter usage.